2015
DOI: 10.1111/tog.12176
|View full text |Cite
|
Sign up to set email alerts
|

Optimal laparoscopic ergonomics in gynaecology

Abstract: Laparoscopic surgery in gynaecology is mainstream and widely practised. While this brings many benefits to the patient, injury to the surgeon is often under-reported. Careful theatre layout and correct instruments minimise the risk to the surgeon. There is a lack of gynaecology-specific guidelines/training in optimal theatre layout and surgeon positioning. This article examines the current available evidence and suggests changes that clinicians can make in order to optimise their working environment. Learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 50 publications
(111 reference statements)
0
18
0
Order By: Relevance
“…The estimated prevalence of musculoskeletal symptoms among gynecologic laparoscopic surgeons was 82% (95% CI, 70%–89%; I 2 , 92%), calculated from a pooled sample size of 1619 surgeons among the 12 studies included (Figure 4). 3,4,8–17 As studies varied in the type of prevalence reported, subgroup analyses were performed to estimate the lifetime, 12‐month, and point prevalence (Figure 5). The estimated lifetime prevalence was 90% (95% CI, 76%–96%; I 2 , 91%), based on data from six studies with a combined sample size of 626 3,4,10,12,13,15 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The estimated prevalence of musculoskeletal symptoms among gynecologic laparoscopic surgeons was 82% (95% CI, 70%–89%; I 2 , 92%), calculated from a pooled sample size of 1619 surgeons among the 12 studies included (Figure 4). 3,4,8–17 As studies varied in the type of prevalence reported, subgroup analyses were performed to estimate the lifetime, 12‐month, and point prevalence (Figure 5). The estimated lifetime prevalence was 90% (95% CI, 76%–96%; I 2 , 91%), based on data from six studies with a combined sample size of 626 3,4,10,12,13,15 .…”
Section: Resultsmentioning
confidence: 99%
“… 3,4,8–17 As studies varied in the type of prevalence reported, subgroup analyses were performed to estimate the lifetime, 12‐month, and point prevalence (Figure 5). The estimated lifetime prevalence was 90% (95% CI, 76%–96%; I 2 , 91%), based on data from six studies with a combined sample size of 626 3,4,10,12,13,15 . The 12‐month prevalence, reported in only one study with a sample size of 67 surgeons, was 63% (95% CI, 51%–73%) 11 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ergonomics in laparoscopic surgery is another fundamental principle, which has been described in detail elsewhere. 10…”
Section: Optimal Exposure and Use Of Assistancementioning
confidence: 99%
“…Appropriate monitor height and position, table height, port placement, and design of handheld instruments can improve poor posture [6][7][8]. Correct ergonomics decreases musculoskeletal disorders, suturing time, and complications [9,10]. Operating rooms can be inhospitable for laparoscopists if ergonomic rules for laparoscopy are not followed.…”
Section: Introductionmentioning
confidence: 99%